Hydrocarbons from near-surface sediments of the Barents Sea north of Svalbard – Indication of subsurface hydrocarbon generation?. (September 2016) - Blumenberg, Martin; Lutz, Rüdiger; Schlömer, Stefan; Krüger, Martin; Scheeder, Georg; Berglar, Kai; Heyde, Ingo; Weniger, Philipp
Abstract: The Barents Sea is considered as an important target for oil and gas exploration, but the petroleum potential of its shelf and slope regions is unknown. Here we present results of a research cruise to the Northern Hinlopen Margin at the transition to the Southern Nansen Basin and the Eastern Yermak Plateau. Multichannel reflection seismic data acquisition, heat flow measurements, and geochemical analyses of near-surface sediments obtained by gravity coring were conducted to study the northern Barents Sea shelf and the early opening of the Nansen Basin and decipher their petroleum potential. Seismic data indicate high thicknesses of up to ∼2000 m of Cenozoic sediments. Heat flow density values in the study area range between 67 and 108 mW/m 2 . The sediment samples were analysed for bulk geochemistry and sorbed hydrocarbon gases and for two sites for extractable hydrocarbons. Data from extractable ( n -alkanes > n -C25 ) and bulk (HI and OI from Rock Eval) organic matter demonstrate predominantly terrigenous organic material, most likely derived from ice-transported allochthonous sediments. None of the sediments revealed substantial amounts of methane in pore waters, arguing against active hydrocarbon seepage in the studied areas. However, thermogenic gases sorbed to the sediment matrix (clay minerals, organic matter and/or carbonates) were found in concentrations of up to 600 ppb (on sediment wet wt. basis). For the samples from the Northern Hinlopen Margin and particularly from the adjacent Nansen Basin, a paleo fluid flow of thermogenic gas is indicated and accompanied by higher n -alkanes with a modal, petroleum-like distribution. δ 13 C values of methane, ethane and propane and gas compositions point at a mainly marine source rock origin of all studied gases with early oil window maturities of the associated rocks (0.6–0.9%VR). From this data an admixture of Type III derived thermogenic gases is indicated for some of the Yermak Plateau sediments for which also the lowest abundances of sorbed gases (50–100 ppb) were observed. Gas geochemical characteristics in the samples with low gas abundances can partially be explained by an input of gases through ice-transport of allochthonous hydrocarbons, which were bound to mature organic matter. For a site on the Northern Hinlopen Margin NE of Svalbard, right at the southern termination of the Nansen Basin a different situation is indicated. In this area the highest concentrations of sorbed gases most likely derived from sediments with an early-oil window maturity and a marine kerogen Type II-typical isotopic distribution. At this location a pseudo well was constructed from 2D seismic data for reconstruction of thermal and maturity evolution. The simulation results indicate that an Early to Middle Eocene source rock would be in the early oil window since the Early Miocene. A possible source rock here and in the circum-Arctic region could have been formed by Azolla algae and other flourishing primary producers. Highlights: Southern Nansen Basin and Yermak Plateau sediments studied for gas geochemistry. Low concentrations of pore water methane exclude active gas seepage. δ 13 C of sorbed hydrocarbons suggest paleoseepage from mostly type II organic matter. 2D seismic data demonstrate up to 2000 m sedimentary cover. 1D-modelling and heat flow support locally oil window maturity of Eocene sediments.